Seroprevalence and associated factors of trichinellosis in indigenous pigs and rural communities in Northern Vietnam - Sinh Dang-Xuan; Nga Vu-Thi; Dung Do-Trung; Trang Le-Thi-Huyen; Ngoc Pham Thi; Unger, Fred (International Livestock Research Institute, 2022)
Objectives: The study aim was to identify seroprevalence of trichinellosis and associated factors of both indigenous pigs and humans in Northern communities in Vietnam. Materials and methods: A cross-sectional study was conducted in 2021 in ten communes in Bac Yen district (Son La province) and Bat Xat district (Lao Cai provinces). A total of 1,000 serum samples (500 indigenous pigs and 500 community participants) was collected and tested using a commercial ELISA test kit (Priocheck, ThermoFisher). Structure questionnaires were also used to interview selected pig owners and sampled community members regarding pig raising practice, eating behavior and disease knowledge and prevention. Results: The result shows that seroprevalence of trichinellosis in indigenous pigs and humans were 9.0% (45/500, 95%CI: 6.7-11.9) and 13.4% (67/500, 95%CI: 10.6-16.8), respectively. Trichinella seroprevalence in human was significantly higher in Son La (16.7%) compared to in Lao Cai (8.5%), but not for seroprevalence in pigs. Factors associated with trichinellosis seroprevalence in human were raising pigs’ activities (p=0.029, Fisher test) and eating raw vegetable behavior (p=0.007, Chi square test). While factors associated with trichinellosis seroprevalence in pigs were farmer’s knowledge about trichinellosis (p=0.033, Chi-squared test). Conclusion: Seroprevalence in both pigs and humans in northern Vietnam were relatively high, especially in the endemic province, which suggested the possibility of Trichinella spp. circulation in the community and indigenous pigs. Animal and public health awareness for the northern communities and pig farmers, i.e., using One health approach, are necessary to improve prevention and control this disease.